GROWTH AND YIELD TEST OF PAKCOY PLANTS BY UTILIZING WHITE OYSTER MUSHROOM BAGLOG WASTE AND BIOCHAR COMPOST AS PLANTING MEDIA - Ndua, Natalia Desy Djata; SERAN, MARSELINA HOAR; Tobing, Wilda Lumban; Bria, Deseriana (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Pakcoy productivity decreases every year due to the use of lowquality soil as a planting medium. The aim of this research is to determine the growth and yield tests of pakchoy plants (Brassica rapa L.) by using white oyster mushroom baglog waste and biochar compost as a planting medium. This research consisted of three times for a total of 36 experimental units. The results of the research showed that there was an interaction between white oyster mushroom baglog waste and biochar compost on the parameters of plant height 14-35 DAP, number of leaves 14-35 DAP, root fresh weight, root dry weight, plant fresh weight, and plant dry weight with the best treatment. is a no-waste white oyster mushroom baglog with 1.25 kg biochar compost. The treatment of white oyster mushroom baglog waste had a significant effect on all growth parameters with the best results being without providing white oyster mushroom baglog waste. Providing 1.25 kg biochar compost had a significant effect on all growth and yield parameters with the best treatment being 1.25 kg biochar compost.